New Approach of QuEChERS and GC-MS Triple-Quadrupole for the Determination of Ethyl Carbamate Content in Brazilian cachaças - Guerreiro, Tatiane Melina; Ozawa, Kumi Shiota; Lima, Estela de Oliveira; Melo, Carlos Fernando Odir Rodrigues; de Oliveira, Diogo Noin; Triano, Simone Pereira do Nascimento; Catharino, Rodrigo Ramos (Frontiers in Nutrition, 2018)
Cachaça is a popular spirit produced in Brazil, obtained by distillation of fermented sugar cane. Among the contaminants arising from production, ethyl carbamate is a carcinogenic compound that occurs naturally in fermented foods and beverages; in Brazil, the maximum limit established by current legislation is 150 µg L-1. Quality control is usually performed using gas chromatography; however, robustness and reproducibility of quantitative results may be severely impaired, as the addition of 6-30 g L-1 of sucrose is a common procedure for taste standardization, directly interfering in the results. This work describes the development of a novel method to improve ethyl carbamate quantification in cachaças using a new approach of QuEChERS extraction based on salting-out phenomenon, to effectively separate ethanol from sugar-containing water. Eighteen different brands of cachaça were analyzed. The proposed methodology was able to eliminate components that contaminate the sample flow path in the GC system, while improving precision and accuracy by using a triple-quadrupole approach, in comparison with the methodology usually employed: direct analysis of cachaça samples with no sample prep. Results indicate that this approach is more effective due to the removal of sugar content, with no impact in costs per analysis.